Nutrition-related practices and attitudes of Kansas skipped-generation caregivers and their grandchildren - Murray, Bethany Joann (Kansas State University, 2007)
Purpose: Skipped-generation households are increasing both nationally and in Kansas. This qualitative study explored the nutrition-related practices and attitudes of Kansas older skipped-generation caregivers and the children under their care. Design and Methods: Twenty-three Kansas caregivers representing 19 households were interviewed about a range of topics using a semi-structured approach. Interview transcriptions were content analyzed. Results: Nutrition-related practices and attitudes changed over time. Compared to when they were parenting the first time, skipped-generation caregivers reported that they are more nutrition and food safety conscious and have shifted in their parenting style. Their grandchildren appeared to be adversely affected by an on-the-go lifestyle and the use of more electronics. Caregiver sources of child feeding advice are based mostly on tradition. Caregivers believed that nutrition and safe food handling are important; they held beliefs that nutritious food is expensive; and most did not believe they would use population-specific nutrition education materials. The preferred distribution of nutrition education materials was through grandparent support groups. Implications: Research was exploratory in nature with a limited sample size. This population could benefit from education incorporating topics on infant, child, adolescent, and sports nutrition; healthful recipes and snack ideas; quick and inexpensive healthful meals that are low in fat, sugar, and salt; healthful fast food and packaged food options; the importance of checking the internal temperatures of meat when cooking; ways to feed "picky eaters;" benefits of eating together as a family; tips to limit children's sedentary time; and intergenerational gardening and cooking.
Keywords: Custodial grandparents; qualitative nutrition research; child feeding; eating beliefs; Health Sciences, General (0566)